Emrick, Lance (Robert) - Stevens Fuels Treatment Funds - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2013)
Located in: Fort Collins office files. Robert Emrick's records related Colorado State Forest Service (CSFS) Stevens Fuels Treatment Funds (CAFA) program. Includes: grant application with assessor property information; payment requests; disbursement voucher; program reimbursement requests; cost documentation worksheets; final closeout report with photographic prints; labor and equipment logs; cooperative match project and scope of work reports; and annotated maps.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado